Menimbang Gadai Emas sebagai Instrumen Investasi Syariah - Ahmad Chairul Hadi (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
The increasing of gold prices and high interest of the community to invest in gold responded by Islamic banking through Islamic gold pawning services with the term "gardening gold". This investment is a modification of the mortgage system in Islamic banks and pawnshops. This investment is not neither a product of Islamic banks and Islamic pawnshops. Islamic financial institutions provide only mortgage facilities not including investment to customers. The nature of the gardening gold transaction is to borrow money to pay the storage fee pawned gold and then to expect a rise of the gold price at market exceeding the costs of the bank.DOI: 10.15408/aiq.v4i2.2531